Dilemmas of integrated water resources management implementation in the Awash River Basin, Ethiopia: irrigation development versus environmental flows. (13th October 2020) - Mersha, Adey Nigatu; de Fraiture, Charlotte; Masih, Ilyas; Alamirew, Tena
Abstract: Environmental flows allocation is an intrinsic part of Integrated Water Resources Management (IWRM). This paper analyses socio‐political issues and effects of environmental flows integration on water availability under the context of increased agricultural intensification in an effort to tackle food insecurity. Lack of appropriate framework comprising the procedural requirements and strategic directions as well as prevalence of politically motivated ad hoc development programmes are among major challenges identified. Introducing environmental flows to a perceived satisfactory level would result in a significant increase of unmet irrigation water demand, yet, "productivity first" norm overtakes. This is presumed to be due to skewed focus on irrigation expansion and low awareness on the possible consequences. The particular challenges highlighted generally unveil the inherent contradictions in the IWRM concept putting its claim that the set of principles and entire course stand universally accepted as a means to balance socio‐economic and environmental outcomes under question.